A Squirrel-cage Globoidal Cam Planetary Mechanism - Gong Yan; Cao Jujiang; Zhang Yanhua (Jixie chuandong)
The globoidal cam planetary mechanism is difficult to machine， the assembly precision is difficult to guarantee， and its manufacturing cost is high. These problems are caused by the toroidal structure of the outer annulus cam. A new type of squirrel-cage globoidal cam planetary mechanism is proposed to solve this problem. The new type of mechanism mainly improves the structure of the outer annulus cam in the mechanism. The new structure not only reduces the difficulty of machining the outer annulus cam， but also avoiding the problem that the assembly accuracy is not high due to the outer annulus cam split structure. Through the three-dimensional modeling and motion simulation of squirrel-cage globoidal cam planetary mechanism， the accuracy of the mechanism movement is verified by the simulation results.